2012
DOI: 10.1016/s0140-6736(12)60821-6
|View full text |Cite
|
Sign up to set email alerts
|

Global epidemiology of HIV infection in men who have sex with men

Abstract: Epidemics of HIV in men who have sex with men (MSM) continue to expand in most countries. We sought to understand the epidemiological drivers of the global epidemic in MSM and why it continues unabated. We did a comprehensive review of available data for HIV prevalence, incidence, risk factors, and the molecular epidemiology of HIV in MSM from 2007 to 2011, and modelled the dynamics of HIV transmission with an agent-based simulation. Our findings show that the high probability of transmission per act through r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
1,186
9
27

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,376 publications
(1,256 citation statements)
references
References 94 publications
34
1,186
9
27
Order By: Relevance
“…We do not deny that the 'MSM population', as currently constituted in epidemiological surveillance data, suffers from disproportionately higher levels of HIV and other BBI's: as series of epidemiological studies across a range of national settings have shown (Beyrer et al 2012). But our question relates precisely to the way data are constituted.…”
Section: The Limits Of Epidemiological Modellingmentioning
confidence: 92%
See 1 more Smart Citation
“…We do not deny that the 'MSM population', as currently constituted in epidemiological surveillance data, suffers from disproportionately higher levels of HIV and other BBI's: as series of epidemiological studies across a range of national settings have shown (Beyrer et al 2012). But our question relates precisely to the way data are constituted.…”
Section: The Limits Of Epidemiological Modellingmentioning
confidence: 92%
“…Even in studies where diversity within MSM is recognised the relevance of condom use is marginalised and ultimately, diversity is subsumed in favour of reconfirming the category 'MSM' as high-risk (see Pathela et al 2011: Beyrer et al 2012. Furthermore, assessments of MSM risk are always relational to those calculated for the 'general [heterosexual] population'.…”
Section: The Limits Of Epidemiological Modellingmentioning
confidence: 99%
“…4 Female sex workers (FSW) have an HIV prevalence as high as 60% in South Africa, 5 and limited data put prevalence among men who have sex with men (MSM) at 18% across the continent. 6 The distribution of domestic funding across countries in SSA directly reflects neither disease burden nor financial need, 7 whilst international donors vary in how they prioritise countries; but a better funding configuration has not been offered. Some previous studies have argued for targeting HIV treatment and prevention efforts by geography 8 or risk group, 9 and reaching marginalised high-risk populations is widely viewed as crucial to epidemic control.…”
Section: Introductionmentioning
confidence: 99%
“…1 Even in the context of the broadly generalised HIV epidemics of Southern Sub-Saharan Africa, MSM have been found to carry a higher burden of HIV compared to other age-matched reproductive age men. 2,3 In a recent study of more than 500 MSM in Lesotho recruited via respondent-driven sampling across two urban centers, prevalence was 31.1% in the capital of Maseru and 35.4% in Maputsoe.…”
Section: Introductionmentioning
confidence: 99%